Modulation of disease severity of dystrophic epidermolysis bullosa by a splice site mutation in combination with a missense mutation in the COL7A1 gene - Winberg, Jan-Olof; Hammami-Hauasli, Nadja; Nilssen, Øivind; Anton-Lamprecht, Ingrun; Naylor, Susan L.; Kerbacher, Karen; Zimmermann, Mirjam; Krajci, Peter; Gedde-Dahl, Tobias; Bruckner-Tuderman, Leena (Human molecular genetics, 1997)
Dystrophic epidermolysis bullosa (EBD) is a clinically heterogeneous skin disorder, characterized by abnormal anchoring fibrils (AF) and loss of dermal-epidermal adherence. EBD has been linked to the COL7A1 gene at chromosome 3p21 which encodes collagen VII, the major component of the AF. Here we investigated two unrelated EBD families with different clinical phenotypes and novel combinations of recessive and dominant COL7A1 mutations. Both families shared the same recessive heterozygous 14 bp deletion at the exon-intron 115 boundary of the COL7A1 gene. The deletion caused in-frame skipping of exon 115 and the elimination of 29 amino acid residues from the pro-α1(VII) polypeptide chain. As a result, procollagen VII was not converted to collagen VII and the C-terminal NC-2 propeptide which is normally removed from the procollagen VII prior to formation of the anchoring fibrils was retained in the skin. All affected individuals also carried missense mutations in exon 73 of COL7A1 which lead to different glycine-to-arginine substitutions in the triple-helical domain of collagen VII. Combination of the deletion mutation with a G2009R substitution resulted in a mild phenotype. In contrast, combination of the deletion with a G2043R substitution led to a severe phenotype. The G2043R substitution was a de novo mutation which alone caused a mild phenotype. Thus, different combinations of dominant and recessive COL7A1 mutations can modulate disease activity of EBD and alter the clinical presentation of the patients.
Gesehen am 23.10.2023